Diet and exercise in cognitive function and neurological diseases - Farooqui, Tahira; Farooqui, Akhlaq A.; Ohio Library and Information Network (Hoboken, New Jersey : John Wiley & Sons Inc., 2014)
"Diet and Exercise in Cognitive Function and Neurological Diseases looks at the role and impact that nutrition and activity have on cognitive function and neurological health. The book is divided into the two sections. The first focuses on diet and its impact on neurobiological processes. Chapters focus on the impacts of specific diets, such as the Mediterranean diet, ketogenic and vegan diets, as well as the role specific nutrients, fats, fatty acids, and caloric intake have on neurological health and cognitive function. The second part of the book focuses on exercise, and its role in maintaining cognitive function, reducing neuroinflammatory responses, regulating adult neurogenesis, and healthy brain aging. Other chapters in this section look at the impacts of disease in the management of specific neurological disorders such multiple sclerosis and Parkinson's disease. Collectively, the chapters in Diet and Exercise in Cognitive Function and Neurological Diseases come together to form a timely reference on the neurobiological interplay between diet and exercise on long-term brain health and cognitive function"--Provided by publisher
Includes bibliographical references and index
Keywords: Nutritionally induced diseases; Brain -- Physiology; Aging -- Physiology; Brain -- physiology; Aging -- physiology; Cognition -- physiology; Diet; Exercise; Nervous System Diseases; Electronic books